2010
DOI: 10.2987/09-5979.1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Mosquito Magnet® Liberty Plus Trap on the Human Mosquito Biting Rate under Semi-Field Conditions

Abstract: This study evaluated the efficacy of a commercially available mosquito trap, the Mosquito Magnet Liberty Plus (MM), in reducing human biting rates under semi-field conditions when used alone or with different types of repellents. The MM trap significantly reduced the human biting rate with both laboratory-reared Culex quinquefasciatus and Anopheles gambiae sensu stricto. The MM trap catch did not increase when a mosquito coil was burned but did significantly increase when a skin repellent was applied to the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…Results indicated that the chosen concept could be well accepted by the communities, but it implies the use of insecticides which produce increased resistance in a target mosquito population when used inefÞ-ciently or indiscriminantly (FonsecaÐGonzales et al 2010, Polson et al 2011 and does not comply with the general idea of push and pull as a nontoxic means of pest control (Cook et al 2007). In addition, depending on the concentration used, insecticides can intoxicate the target mosquito and cause it to rest or seek shelter instead of being attracted to a trap and get caught, a behavior that was also observed during the semiÞeld tests by Kitau et al (2010). Our work therefore focused on evaluating non-to low-insecticidal compounds which mediate distance effects without killing or intoxicating the target mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Results indicated that the chosen concept could be well accepted by the communities, but it implies the use of insecticides which produce increased resistance in a target mosquito population when used inefÞ-ciently or indiscriminantly (FonsecaÐGonzales et al 2010, Polson et al 2011 and does not comply with the general idea of push and pull as a nontoxic means of pest control (Cook et al 2007). In addition, depending on the concentration used, insecticides can intoxicate the target mosquito and cause it to rest or seek shelter instead of being attracted to a trap and get caught, a behavior that was also observed during the semiÞeld tests by Kitau et al (2010). Our work therefore focused on evaluating non-to low-insecticidal compounds which mediate distance effects without killing or intoxicating the target mosquitoes.…”
Section: Discussionmentioning
confidence: 98%
“…These Þndings, however, were not conÞrmed in tests with human odors as some of the described agonists and antagonists may have undesirable safety proÞles at higher concentrations that could disqualify them for human use. In 2010, semiÞeld tests evaluated the bite-reducing efÞcacy of the Mosquito Magnet trap in a conÞned area when used in combination with conventional and commercially available repellents (Kitau et al 2010). The use of the trap and a skin repellent led to a signiÞcant decrease in the human biting rates but further modes of application of the repellent component need to be investigated to reduce the personal effort within the presented approach.…”
Section: Discussionmentioning
confidence: 99%
“…A Mosquito Magnet trap produces a continuous and odourless stream of CO 2 , warmth and moisture into the air (Kline, 2006;Kitau et al, 2010;Xue et al, 2010). Traps were set in proximity to potential breeding sites and under canopy in banana plantations and in proximity to animals sleeping areas.…”
Section: Mosquito Collectionmentioning
confidence: 99%
“…Studies in Kenya have identified important techniques for sampling RVF vectors (Tchouassi et al, 2012). Attempts to use such sampling techniques have been found to be useful in mosquito vectors for malaria and filariasis (Mboera et al, 2000a,b;Korgaonkar et al, 2008;Kitau et al, 2010). Inadequate sampling of potential RVF vectors may lead to under-reporting the role of mosquito in transmission and persistence of RVF virus during inter-epidemics period.…”
Section: Introductionmentioning
confidence: 99%
“…However, for some of these, there is not sufficient scientific evidence to support claims of efficacy and/or safety. examples include electronic (ultrasonic) devices (75;76), wristbands, neckbands, and ankle bands impregnated with repellents (40), electrocuting devices (75;77), odour-baited mosquito traps (78)(79)(80), the Citrosa plant (78;81;82), oral vitamin b1 (83), and skin moisturizers that do not contain an approved repellent active ingredient (40). Catmat recommends that these interventions not be used for protection against arthropod bites and related aad.…”
Section: Ineffective Ppmmentioning
confidence: 99%